Analisis akuntabilitas, partisipatif, dan transparansi pengelolaan dana desa berdasarkan Permendagri Nomor 20 Tahun 2018 (Studi kasus Desa Wiau Lapi Barat, Kecamatan Tareran, Kabupaten Minahasa Selatan) - Karundeng, Revio Kevin Brandon; Walandouw, Stanley Kho; Lintong, Diana (Riset Akuntansi dan Portofolio Investasi, 2025)
Village Fund management is a major issue in village development in Indonesia. Regulation of the Minister of Home Affairs Number 20 of 2018 regulates the management of village funds, prioritizing accountability, participation, and transparency. The purpose of this study was to determine and evaluate the accountability, participation, and transparency of village fund management in Wiau Lapi Barat Village, Tareran District, South Minahasa Regency. This study used a qualitative descriptive method and the data collection techniques used were documentation and interviews. This interview involved stakeholders related to village fund management in Wiau Lapi Barat Village. The results of this study conclude that Wiau Lapi Barat Village has made good efforts in transparency, accountability, and participation to manage village funds in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018. However, there are still things that need to be improved in transparency to the community to achieve more optimal village fund management. The results of this study conclude that Wiau Lapi Barat Village has made good efforts in transparency, accountability, and participation to manage village funds in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018. However, there are still things that need to be improved in transparency to the community to achieve more optimal village fund management.